Cross-species genomics reveals oncogenic dependencies in ZFTA/C11orf95 fusion-positive supratentorial ependymomas - Zheng, Tuyu; Ghasemi, David R.; Okonechnikov, Konstantin; Korshunov, Andrey; Sill, Martin; Maass, Kendra K.; Silva, Patricia Benites Goncalves da; Ryzhova, Marina; Gojo, Johannes; Stichel, Damian; Arabzade, Amir; Kupp, Robert; et al. (Cancer discovery, 2021)
Molecular groups of supratentorial ependymomas comprise tumors with ZFTA-RELA or YAP1-involving fusions and fusion-negative subependymoma. However, occasionally supratentorial ependymomas cannot be readily assigned to any of these groups due to lack of detection of a typical fusion and/or ambiguous DNA methylation-based classification. An unbiased approach with a cohort of unprecedented size revealed distinct methylation clusters composed of tumors with ependymal but also various other histologic features containing alternative translocations that shared ZFTA as a partner gene. Somatic overexpression of ZFTA-associated fusion genes in the developing cerebral cortex is capable of inducing tumor formation in vivo, and cross-species comparative analyses identified GLI2 as a key downstream regulator of tumorigenesis in all tumors. Targeting GLI2 with arsenic trioxide caused extended survival of tumor-bearing animals, indicating a potential therapeutic vulnerability in ZFTA fusion-positive tumors. - Significance: ZFTA-RELA fusions are a hallmark feature of supratentorial ependymoma. We find that ZFTA acts as a partner for alternative transcriptional activators in oncogenic fusions of supratentorial tumors with various histologic characteristics. Establishing representative mouse models, we identify potential therapeutic targets shared by ZFTA fusion-positive tumors, such as GLI2.This article is highlighted in the In This Issue feature, p. 2113
Gesehen am 29.10.2021